A Bayesian inference comparing collegiate female cyclists to elite female cyclists from a meta-analysis - Wyatt, F. B.; Dhimar, M.; Shah, Y. (International Journal of Exercise Science, 2016)
9(3): 368-375, 2016. The aim of this study was to evaluate the physiological characteristics of competitive, collegiate female cyclists (CFC) to data of elite female cyclists (EFC) obtained from a meta-analytic review. Eleven (n=11) CFC volunteered as subjects. Subjects signed a university approved informed consent. Means and standard deviation (+ SD) were obtained from the following measurements: age (y), 22.5± 5.1; height (cm) 167.22 ± 6.2; body mass (kg) 63.78 ± 9.71; body fat (%) 22.9 ± 3.6. Subjects performed a maximal cycling ergometer test to volitional fatigue. Maximal oxygen consumption (VO2 max, mL*kg1*min.-1) was analyzed using a gas analyzer. VO2 max, maximal blood lactate (mM), maximal power (W), lactate threshold (mM), ventilatory threshold (VT, % of maximal) and heart rate threshold (HRT, % of maximal) were used to compare the performance of CFC to the data of EFC. An independent samples t-Test compared measures of the CFC vs. EFC. Alpha was set a priori at p = 0.05. Results indicate comparisons between CFC vs. EFC, respectively: body fat %, 22.9 (3.6)* vs 15.2( 3.3); VO2 max (mL/kg/min), 58.07(6.94)* vs 52.5 ( 5.5); max power (W) 275.0( 42.5 ) vs 450.7( 256)* ;lactate threshold (mM) 3.74(0.79)* vs 2.8 ( 0.28); VT (%) 87.0( 4.1)* vs 73.2 ( 9.8) and HRT (% max) 93.1( 2.2)* vs 79.7. There were significant differences *(p< 0.05) in the aforementioned measures. Results indicate differences between CFC vs. EFC. These differences were favorable in relation to performance with both CFC and EFC.